The Benefits of Gamification in the English Learning Context - Eka Fajar Rahmani (IJEE (Indonesian Journal of English Education), 2020)
ABSTRACTThis study aims at displaying the results of reviewing research-based articles about gamification in the context of learning English. The concept of games has changed from a self-entertainment into an edutainment through adjustments and modifications. This notion is adapted by teachers in big countries such as Poland, China, and the US to enhance their English class with surprisingly ensuing positive results (Rothwell & Shaffer, 2019). These results have triggered the writer to find out more about the benefits of gamification and to conduct qualitative research through the review process. The writer collected and analyzed thirteen relevant articles from journals and websites. The results indicated that gamification indeed brought benefits to students. The foremost results included motivation improvement, promoting positive attitudes and better performances, fostering 21st-century skills and better cognitive achievements, encouraging social interaction and independencies, and improving competitiveness among students during the learning process.ABSTRAKPenelitian ini bertujuan untuk memaparkan hasil dari telaah artikel berbasis riset tentang gamifikasi pada konteks pembelajaran Bahasa Inggris. Konsep permainan telah berubah dari hiburan mandiri menjadi edutainment melalui penyesuaian dan modifikasi. Konsep ini, terutama permainan online, diadaptasi oleh para guru di negara-negara besar seperti Polandia, China, dan US untuk meningkatkan aktifitas kelas Bahasa Inggris mereka dengan yang hasil positif yang mengejutkan (Rothwell & Shaffer, 2019). Hasil ini menjadi motivasi penulis untuk menggali lebih dalam tentang manfaat gamifikasi dalam pembelajaran Bahasa Inggris sehingga penulis melakukan penelitian kualitatif melalui proses review. Penulis telah mengumpulkan dan menganalisa tiga belas artikel yang relevan dari jurnal dan situs web. Hasil analisa menunjukkan bahwa gamifikasi memang bermanfaat bagi siswa. Manfaat yang paling utama yaitu meningkatkan motivasi dan penampilan yang baik, mengembangkan keterampilan Abad 21, mendorong interaksi social dan kebebasan, serta meningkatkan daya saing antar siswa selama pembelajaran. How to Cite: Rahmani, E.F. (2020). The Benefits of Gamification in the English Learning Context. IJEE (Indonesian Journal of English Education), 7(1), 32-47. doi:10.15408/ijee.v7i1.17054